solve by formula method
3 {x}^{2}  - 6x + 12 = 0

Question

solve by formula method
3 {x}^{2}  - 6x + 12 = 0

in progress 0
Katherine 2 months 2021-07-27T14:46:36+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-27T14:47:46+00:00

    Step-by-step explanation:

    The equation 3x² – 6x + 12 = 0

    is of the form ax² + bx + c = 0,

    where,

    a = 3

    b = -6

    c = 12

    As per formula,

    \sf \quad \ \ x = \dfrac{- b ± \sqrt{b^2 – 4ac}}{2a} x=

    2a

    −b±

    b

    2

    −4ac

    \sf \Rightarrow x = \dfrac{-(-6) ± \sqrt{(-6)^2 – 4(3)(12) }}{2(3)}⇒x=

    2(3)

    −(−6)±

    (−6)

    2

    −4(3)(12)

    \sf \Rightarrow x = \dfrac{6 ± \sqrt{36(-3)}}{6}⇒x=

    6

    36(−3)

    \sf \Rightarrow x = \dfrac{6 ± 6 \sqrt{-3}}{6}⇒x=

    6

    6±6

    −3

    \sf \Rightarrow x = \dfrac{\cancel6( ± \sqrt{-3})}{\cancel6}⇒x=

    6

    6

    −3

    )

    \sf \Rightarrow x = 1 ± \sqrt{3 \times -1}⇒x=1±

    3×−1

    \sf{ \Rightarrow x = 1 ± \sqrt{3}}i⇒x=1±

    3

    i

    \begin{gathered} \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \rm Thank \ You!\end{gathered}

    Thank You!

    0
    2021-07-27T14:48:13+00:00

    The equation 3x² – 6x + 12 = 0

    is of the form ax² + bx + c = 0,

    where,

    • a = 3
    • b = -6
    • c = 12

    As per formula,

     \sf \quad \ \ x = \dfrac{- b ± \sqrt{b^2 - 4ac}}{2a}

     \sf \Rightarrow x = \dfrac{-(-6) ± \sqrt{(-6)^2 - 4(3)(12) }}{2(3)}

     \sf \Rightarrow x = \dfrac{6 ± \sqrt{36(-3)}}{6}

     \sf \Rightarrow x = \dfrac{6 ± 6 \sqrt{-3}}{6}

     \sf \Rightarrow x = \dfrac{\cancel6( ± \sqrt{-3})}{\cancel6}

     \sf \Rightarrow x = 1 ± \sqrt{3 \times -1}

     \sf{ \Rightarrow x = 1 ± \sqrt{3}}i

     \\  \\  \\  \\  \\  \\  \\  \\  \\  \\  \rm  Thank \ You!

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )